Corporate Governance and Company Survival - Chancharat, Surachai; Chancharat, Nongnit (Humanities, Arts and Social Sciences Studies, 2013)
The main purpose of this paper is to review the literature on the empirical methodologies utilized in bankruptcy prediction and the potential predictors of firm surviving. The paper has reviewed and briefly discussed previous literature examining firm survival or failure in various countries e.g. Australia, China, Germany, Taiwan, U.S.A. and Thailand using various research methodologies such as logistic regression, multivariate discriminant analysis, neural network, survival analysis and etc. These studies have been conducted both within the qualitative and quantitative framework. It can be seen that previous studies have been using various empirical methodologies in exploring the issue regarding company survival. Future research could improve upon this current research in various aspects. Some doubts may cast on the appropriateness of model specification and the omission of important variables in previous studies. Thus, more future research incorporated other feasible variables is needed for model validation. The examples of those possible variables are the qualitative variables e.g. ownership structure data, specifically, gender, education and attitudes.